Feminist metafiction and the evolution of the British novel - Peters, Joan Douglas, 1949- (University Press of Florida, 2002)
''This is the best book of feminist narratology to appear in the past ten years. A genuine advance in the field of the history of British fiction.''--Robyn R. Warhol, University of Vermont''Ambitious in scope, meticulously argued, an innovative approach to canonical novels, newly viewed through the lenses of metafiction, revisionary history of the novel, and feminist narratology.